The Effects of Healthy and Unhealthy Food on Female Body Image and Mood State - Hayes, Jacqueline (Tufts Archival Research Center, 2005)
In a society now plagued with both obesity and eating disorders, the topic of female body image has become particularly salient. Historically believed to be a trait characteristic, research has shown that female body image can be impacted by day-to-day events, including food intake, especially in those with a restrained eating style. The present study examined this phenomenon in more detail, specifically with regards to typically healthy and unhealthy foods and their effect on state body image. Female participants were recruited to partake in an experiment believed to assess the effect of certain foods on cognition and were given a healthy or unhealthy snack or were placed in a control no food condition. The healthy and unhealthy foods were of similar caloric content. Subjects participated in three cognitive tasks but were also asked to report their state body image, mood, perceived body size both before and after eating the snack. Additionally, they answered a number of other surveys designed to hide the true interest of the study. Results indicate that intake of unhealthy food impacts female body image in a negative manner whereas intake of a healthy food and no food at all elicit no change. Furthermore, after eating an unhealthy snack women displayed a decrease in depressive mood state. Additional research on restraint, BMI, and healthy eater status is discussed.